THE ROLE AND IMPORTANCE OF THE EDUCATIONAL PROCESS IN EDUCATION - Khasanova Gulinur Abdijalol's daughter (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: In this article, what is the main goal and content of the education process, the inexplicable connection between education and education, and the general education of the young generation information is provided.